37.1k views
0 votes
(3xy - 1) (4xy + 2) Please help asap!

User Evelie
by
7.2k points

2 Answers

3 votes
Use the FOIL method so,
12xy^2+6xy-4xy-2 and simplify by adding like terms to get —> 12xy^2+2xy-2
User Thelsdj
by
8.0k points
1 vote
Hey there!

Like I commented on your previous questions, you would have to use distributive property.

Multiply......
3xy × 4xy = 12x²y²
3xy × 2 = 6xy
-1 × 4xy = -4xy
-1 × 2 = -2

Add all those terms
12x²y² + 6xy - 4xy - 2
add the like terms

12x²y² + 2xy - 2
Hope this helped :)



User Timofei Davydik
by
7.8k points